2019
DOI: 10.22159/ijap.2019v11i4.32331
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Development of Immediate Release Pellets of Tadalafil: Solidification Approach for Nanosuspension

Abstract: Objective: Nanosuspension is known to enhance the saturation solubility and dissolution velocity of poorly soluble drugs owing to the increased surface area of nanosized particles. Stability of these solubility enhancing systems can be improved by converting them into solidified forms. To simultaneously achieve enhanced dissolution and improved stability, an attempt has been made to increase the dissolution rate of poorly soluble drug tadalafil by formulating immediate release pellets of its nanosuspension.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…After optimisation of the formula, the immediate release pellets of canagliflozin were prepared by applying 2 3 factorial design using nanosuspension as a binder. [13] From the formulation and production result, it was observed that microcrystalline cellulose was used as pelletizing aids and sodium starch glycolate as super disintegrant, gave acceptable spherical pellets with good yield, low friability and satisfactory flow properties. Based on the observations, 30% of MCC, 10% of SSG and spheronization speed of 800 rpm with time 10 mm were selected as formulation and process parameters.…”
Section: Preparation Of Immediate Release Pelletsmentioning
confidence: 99%
See 2 more Smart Citations
“…After optimisation of the formula, the immediate release pellets of canagliflozin were prepared by applying 2 3 factorial design using nanosuspension as a binder. [13] From the formulation and production result, it was observed that microcrystalline cellulose was used as pelletizing aids and sodium starch glycolate as super disintegrant, gave acceptable spherical pellets with good yield, low friability and satisfactory flow properties. Based on the observations, 30% of MCC, 10% of SSG and spheronization speed of 800 rpm with time 10 mm were selected as formulation and process parameters.…”
Section: Preparation Of Immediate Release Pelletsmentioning
confidence: 99%
“…In vitro dissolution studies [13,19] In vitro drug release studies of pellets were performed using the USP Apparatus I (basket) at a speed of 75 rpm in 900 ml of 0.75% w/v of SLS and the medium at 37.0±2°C. Canagliflozin is soluble in many organic solvents (methanol, dimethyl sulfoxide) and insoluble in aqueous media and freely soluble in 0.75% w/v of SLS.…”
Section: Tan (θ) = H/rmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a pressing need to develop colonspecific oral solid dosage form. In this framework, pellets offer advantages such as predictable gastric transit time, minimum local irritation, enhanced bioavailability, reduced dose dumping and readily coatable which render them suitable for controlled drug delivery [10][11][12][13][14]. Prolonged residence time, specific pH level and microbial environment of colon represent the key elements for colon targeting [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the development of prominent colonspecific oral solid dosage form is an extreme dictate today. In this scaffold, multiparticulate system must be utilized due to its advantages such as predictable gastric transit time, minimum local irritation, enhanced surface area, reduced dose dumping and readily coatable which render them suitable for controlled drug delivery [10][11][12][13][14] . Prolonged residence time, specific pH level and microbial environment of colon represent the input essentials for colon targeting 15 .…”
mentioning
confidence: 99%